Influence of IL10 (rs1800896) Polymorphism and TNF-α, IL-10, IL-17A, and IL-17F Serum Levels in Ankylosing Spondylitis - Braga, Matheus; Lara-Armi, Fernanda Formaggi; Neves, Janisleya Silva Ferreira; Rocha-Loures, Marco Antônio; Terron-Monich, Mariana de Souza; Bahls-Pinto, Larissa Danielle; de Lima Neto, Quirino Alves; Zacarias, Joana Maira Valentini; Sell, Ana Maria; Visentainer, Jeane Eliete Laguila (Frontiers in Immunology, 2021)
Ankylosing spondylitis (AS) is a chronic autoimmune inflammatory disease that mainly affects the axial and sacroiliac joints. Single nucleotide polymorphisms (SNPs) in genes encoding cytokines have been associated with AS, which can interfere with the production of these cytokines and contribute to the development of AS. In order to contribute to an understanding of the pathology of AS, our objective was to investigate a possible association of the IL10 -1082 A>G SNP (rs1800896) with AS, and to evaluate the serum levels of TNF-α, IL-10, IL-17A and IL-17F in AS patients and controls comparing them with their respective genotypes (TNF rs1800629, IL10 rs1800896, IL17A rs2275913 and IL17F rs763780). Patients and controls were selected from the Maringá University Hospital and the Maringá Rheumatism Clinic, in Paraná State, Southern Brazil, and they were diagnosed by the ASAS Criteria. In total, 149 patients and 169 controls were genotyped for the IL10 -1082 A>G polymorphism using a polymerase chain reaction with sequence specific primers (PCR-SSP); the measurement of TNF-α serum levels was performed through the immunofluorimetric test and IL-10, IL-17A and IL-17F using an ELISA Test. There was a high frequency of the IL10 -1082 G allele in AS patients compared to controls with an odds ratio of 1.83 and 95% confidence interval of 1.32–2.54, and a significant difference in the genotype frequencies of the IL10 -1082 A/G+G/G between patients and healthy controls, with an odds ratio of 3.01 and 95% confidence interval of 1.75–5.17. In addition, increased serum levels of IL-10 were observed in AS patients 2.38 (IQR 0.91) pg/mL compared to controls 1.72 (IQR 0.93) pg/mL (P=0.01). Our results also showed an association between IL17F rs763780 C/T+T/T genotypes and increased serum levels of IL-17F in patients with AS and also in controls. We can conclude that patients with the A/G and G/G genotypes for -1082 A>G (rs1800896) in the IL10 gene are three times more likely to develop AS, that the serum level of IL-10 was higher in AS patients and that the IL17F rs763780 polymorphism can affect the levels of IL-17F in the serum of patients and controls in the same way.